HUBUNGAN POWER OTOT LENGAN DAN BAHU DENGAN HASIL ACCURACY SMASH PADA TIM BOLA VOLI PUTRI SMA NEGERI OLAHRAGA PEKANBARU - August, Kristi; ', Saridah; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This Research based on the fact that the results of smash accuracy atFemale Volley Ball team of Sports Senior High School was less accurate. It was evidentfrom the results of the matches in the follow have not achieved good results. One factorthat affected smash accuracy results at female volleyball team of Sports Senior HighSchool Pekanbaru, the factors that caused less success in doing smash was coordinatedof hand movements when hitting the ball. And also lack of arm muscle and shoulderpower when doing smash, then smash which can be done easily in the block (prevented)by the opposing team, and smash that was less effective, easy to add point of youropponent. The aim in this research was to determine the correlation between armmuscle and shoulder power and smash accuracy at female volley ball teamof sports senior high school Pekanbaru. The population in this research wasFemale volleyball team of Sports Senior High School Pekanbaru totaling 13 people.The sampling technique in this research was total sampling technique. Instruments ofthis research was testing of arm muscle and shoulder power, using Two-Hand MedicinePut ball and smash accuracy test used accuracy of number as the target of smash. Thedata was analyzed by product moment correlation. Based on the results of research, itcan be concluded that the results of the calculation of the correlation between the armmuscle and shoulder power (X) and smash accuracy results (Y) is obtained r count=0.912 while r table at significant level Î± = 0,05 namely 0,576. It means in this casethere is a correlation between arm muscle and shoulder power (X) and smash accuracyresults (Y), so that Ha is received and H0 is rejected.Keywords: Arm muscle and shoulder power,Smash accuracy